The Effect Of Accrual Reliability, Debt Level And Cash Flow Volatility On Earnings Persistence - Komang Ayu Trisna Dayanti; I Gusti Agung Prama YOGA; Gusti Ayu Intan Saputra RINI (Indonesia Strategic Sustainability, 2021)
This research is entitled â€œThe Effect of Accrual Reliability, Debt Level and Cash Flow Volatility on Earnings Persistenceâ€. The research question is â€œIs the persistence of earnings is affected by accrual reliability, debt levels and cash flow volatility? The research objective is to examine empirically the effect of accrual reliability, debt levels and cash flow volatility on the earnings persistence. Accrual reliability, level of debt and cash flow volatility are independent variables in this study while earnings persistence is the dependent variable. This study used secondary data in the form of annual financial statements of sample companies, namely basic industry and chemicals sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sample selection method used was purposive sampling method. In total, there were two 12 sample companies in this study. This study used multiple linear regression data analysis technique including classical assumption test, F-statistical test and hypothesis testing. The results showed the accrual reliability and cash flow volatility had no effect on earnings persistence, while the level of debt had a positive effect on earnings persistence, and therefore, the second hypothesis is acceptable.